Distributed DBP: A (m,k)-firm based distributed approach for QoS provision in IEEE 802.15.4 networks - Tiago Semprebom (2009)
IEEE 802.15.4/Zigbee is one of the most widespread Wireless Sensor Network technologies. It may work either in beacon-enabled mode or in beaconless mode. When operating in beacon-enabled mode, it divides the superframe in sixteen equally-sized time slots, where the request for slot allocation is achieved through a CSMA/CA approach. This allocation method does not allow the provision of any service differentiation scheme, which is required for the transfer of time constrained messages. This paper proposes a QoS provision approach with minimal changes to existing protocols. Our approach improves the CSMA/CA algorithm by assigning decentralized priorities based on the (m,k)-firm task model. In this paper, a set of experimental results is presented and compared with the traditional approach currently offered by the standard. This set of experiments highlight the promising behavior of the proposed approach, when dealing with high network load scenarios. Â©2009 IEEE.